Variation in Physico-Anatomical Properties of Dalbergia sissoo Roxb. ex DC. Wood procured from local markets of Himachal Pradesh - Sunny, Pavin Praize; Dutt, Bhupender; Sharma, Kulwant Rai; Heena; Sumthane, Yogesh Yadavao (Indian Forester, 2019)
The study revealed significant variation in physical and mechanical properties of wood of shisham (Dalbergia sissoo) collected from different timber market sites. The maximum moisture content (20.170%) was observed in the wood samples of Nalagarh site. Highest specific gravity of (0.644) was observed in Dattowal and lowest (0.748) in Nalagarh site. Maximum vessel diameter (0.126 mm), fibre diameter (0.020 mm) and fibre length (1.66 mm) was found in the wood samples from Ghumarwin, Dattowal and Ghumarwin respectively.